The current management of sarcoidosis - Kirkil, Gamze; Baughman, Robert P. (Edizioni Minerva Medica, 2016)
Sarcoidosis is a multisystem granulomatous disease which has a large variability in outcome. So, treatment options range from none to systemic medications. Although the indications for medical therapy of sarcoidosis are controversial, standard therapy for symptomatic, progressive disease consists of corticosteroids. Systemic therapy is clearly indicated for cardiac disease, neurologic disease, eye disease not responding to topical therapy, and hypercalcemia. Although steroids remain the first-choice therapeutic in sarcoidosis, long-term use is associated with toxicity. Refractory cases, with steroid resistance or steroid-induced adverse effects, require alternatives to glucocorticosteroids. Several cytotoxic agents have been used as steroid sparing or replacements for corticosteroids. Methotrexate is most commonly used as a second-line treatment option as a steroid sparing agent. It has also been proposed as a first option in selected cases of neuro and cardiac involvement. Other commonly described agents in this group are: azathioprine, leflunomide, and mycophenolate mofetil. Anti-TNF monoclonal antibodies are now widely used for management of sarcoidosis. There are several TNF-alpha inhibitors available, however not all successful in sarcoidosis. Treatment with TNF-alpha inhibitors etanercept or golimumab did not show positive outcomes in patients with sarcoidosis. Infliximab has been the most widely studied anti-TNF antibody that showed positive outcomes. An alternative treatment option for sarcoidosis is anti-malarial agents (chloroquine and hydroxychloroquine) that were found to be steroid sparing in chronic pulmonary disease. Another option is Achtar gel, but the efficacy, low cost, and wide availability of corticosteroids have relegated ACTH theraphy to a third-line or fourth-line option at present.
Keywords: Prednisone; Methotrexate; Azathioprine; Infliximab